2018
DOI: 10.5688/ajpe6361
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on an Interprofessional Course Involving Pharmacy and Dental Students in a Dental Clinic

Abstract: To assess the effect of a dental clinical rotation program involving pharmacy students and dental students. An interprofessional education (IPE) course was offered as an elective to second-year pharmacy students and required for third-year dental students. The course included two in-class sessions, one online lecture, and five clinic sessions. Program evaluation analyses included a comparison of participating versus nonparticipating students on a knowledge survey of pharmacotherapy and IPE, and a descriptive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…It would be useful to compare our results with findings from other health professions concerning the frequencies with which these programs engage in IPE and with which disciplines they collaborate most often. However, while several studies have assessed students’ IPE‐related attitudes in dentistry, 25 29 medicine, 22 , 25 , 30 nursing, 27 , 31 33 and pharmacy, 26 , 29 the results of studies with program directors or deans are much less available. In 2012, Formicola et al published a survey of dental school deans 15 .…”
Section: Discussionmentioning
confidence: 99%
“…It would be useful to compare our results with findings from other health professions concerning the frequencies with which these programs engage in IPE and with which disciplines they collaborate most often. However, while several studies have assessed students’ IPE‐related attitudes in dentistry, 25 29 medicine, 22 , 25 , 30 nursing, 27 , 31 33 and pharmacy, 26 , 29 the results of studies with program directors or deans are much less available. In 2012, Formicola et al published a survey of dental school deans 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists collaborate with dentists in a variety of ways, many of which fall outside the traditional dispensing role of the pharmacist. A review of the literature has identified pharmacists in academic dental practice settings providing medication reconciliation services, antimicrobial stewardship, assisting in appropriate opioid prescribing, facilitating interprofessional education, didactic lecture, and smoking cessation counseling 1–13 . Choi et al.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…A review of the literature has identified pharmacists in academic dental practice settings providing medication reconciliation services, antimicrobial stewardship, assisting in appropriate opioid prescribing, facilitating interprofessional education, didactic lecture, and smoking cessation counseling. [1][2][3][4][5][6][7][8][9][10][11][12][13] Choi et al described pharmacists having a positive impact on improving the accuracy of patient medications in the dental record. 1 Gross described an antibiotic stewardship effort between dentists, pharmacists, and physicians in an academic dental practice that resulted in a decrease in antibiotic prescribing.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Despite the identified benefits of pharmacist-dentist interprofessional collaboration, a review of the literature illustrates that routine collaboration between the professions is lacking. 1 , 5 , 12 , 20 , 23 28 . Thus far there have only been six studies published in this area.…”
Section: Introductionmentioning
confidence: 99%
“…12 , 20 , 25 , 26 A fifth and sixth study described two different IPE models between dentists and pharmacists in a university dental clinic setting. 27 , 28 The interprofessional team in the study by BranchMays et. al., assisted in identifying drug therapy problems and acquiring primary care metrics (diabetes status, tobacco use, blood pressure and pulse), a need that is rarely met in dental clinics.…”
Section: Introductionmentioning
confidence: 99%